Epidemiological analysis of 556 procedures of open thoracoabdominal aortic aneurysm repair in the Public Health System in the largest Brazilian city - Anacleto,Alexandre Maierá (2022)
ABSTRACT Objective Despite the development of endovascular procedures, open repair remains the gold standard for the treatment of aortic thoracoabdominal aneurysms and some type B dissections, with well-established good outcomes and long-term durability at high-volume centers. The present study described and analyzed public data from patients treated in the public system in a 12-year interval, in a city where more than 5 million inhabitants depend on the Public Health System. Methods Public data from procedures performed between 2008 and 2019 were extracted using web scraping techniques. The variables available in the database include sex, age, elective or emergency hospital admission, number of surgeries, in-hospital mortality, length of stay, and information on reimbursement values. Results A total of 556 procedures were analyzed. Of these, 60.79% patients were men, and 41.18% were 65 years of age or older. Approximately 60% had a residential address registered in the municipality. Of all surgeries, 65.83% were elective cases. There were 178 in-hospital deaths (mortality of 32%). In the elective context, there were 98 deaths 26.78% versus 80 deaths (42.10%) in the emergency context (p=0.174). Mortality was lower in the hospitals that performed more surgeries. A total of USD 3,038,753.92 was paid, an average of USD 5,406.95 for elective surgery and USD 5,074.76 for emergency surgery (p=0.536). Conclusion Mortality was no different between groups, and hospitals with higher volume presented more favorable outcomes. Specialized referral centers should be considered by health policy makers.